PUSAT KERAJINAN ANYAMAN PURUN DAN ECENG GONDOK DI KABUPATEN HULU SUNGAI UTARA - Siti Aisyah; Mohammad Ibnu Saud (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2026)
Hulu Sungai Utara Regency possesses significant potential in the local craft industry, particularly in products derived from wetland-based materials such as purun and water hyacinth weaving. However, this potential is not supported by adequate facilities for product promotion and marketing. This condition highlights the need for a facility capable of integrating promotional, marketing, educational, and empowerment functions within a unified architectural system. In response to this issue, the Craft Empowerment Hub concept is applied, integrating economic, social, and cultural aspects through a functional-architecture-based design approach. Through an analysis of activity patterns as the primary basis for determining spatial requirements, circulation, and zoning, the design produces facilities that include a gallery space for promotion, workshop spaces for education, and craft kiosks for direct marketing activities.